A Conditioned Exchange - Fredrik Torisson (Footprint)
The emergence of financial institutions such as the exchanges or bourses of northern Europe in the sixteenth and the seventeenth centuries made possible the emergence of speculation in financial instruments. Speculation evolved into a game with its own logic, and the implied ethos of the speculator prioritised abstract notions and self-interest.